Case report: Bilateral parotid abscess in a 54-day-old infant - Huang, Lilin; Yang, Xiaole; Peng, Shumei; Li, Ronghan (Frontiers in Pediatrics, 2023)
Acute parotid abscess (PA) is rare in children and is prone to occur in neonates or preterm infants with high risk factors. Sporadic cases with unilateral PA have been reported in older children. Here, we report a 54-day-old child who developed bilateral PA due to Staphylococcus aureus infection. The infant showed bilateral cervical lymphadenopathy initially following a 13-valent pneumococcal conjugate vaccine (PCV13). However, bilateral PA developed 6 hours after he was diagnosed with lymphadenitis on Day 9 of illness. PA progression from cervical lymphadenitis so quickly is rare. He recovered quickly under treatment with appropriate antibiotics based on susceptibility testing and surgical incision and drainage.